Student’s Perception Toward E-Learning During Covid-19 - Fathul Zannah; Noormaliah Noormaliah (Journal on Teacher Education, 2022)
Currently, the condition of the world, including Indonesia, is facing the Corona Virus 19 pandemic that has hit the world since the beginning of 2020 causing a tremendous impact in all aspects of human life, including from the education sector where learning is carried out through online or e-learning. The purpose of this study was to determine students' perceptions of the English language education study program STKIP PGRI Banjarmasin towards online learning applied at STKIP PGRI Banjarmasin. Researchers get data for this study from questionnaires and interviews. The questionnaire contains students' perceptions of online lectures which are divided into several indicators. The results of the questionnaire were re-confirmed through interviews with several students and lecturers. This type of research is descriptive qualitative with a survey focus to describe student perceptions of online learning or e-learning in the future. The results of this study indicate that 71% of students agree with online lectures conducted by STKIP PGRI Banjarmasin and 29% of students disagree with online lectures conducted by STKIP PGRI Banjarmasin.